CORPORATE CRIMINAL LIABILITY IN LAW ENFORCEMENT AGAINST PREMANISM - Albert Sanchez Sebayang; Zulkarnein Koto; Marsudin Nainggolan (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
The practice of thuggery carried out by corporations is often found in the loan repayment process. This had resulted in the mushrooming of debt collector businesses, which generally employed high-profile ex-convicts who were used as collateral to intimidate other parties. In this study, the type of research used is normative juridical research using a law approach and a case approach. From the results of the study, it can be concluded that the enforcement of corporate criminal law against thuggery activities in the four cases studied by the authors was carried out by applying a penal policy (repressive effort). Repressive efforts were made against the Defendants by making arrests and then examining them for questioning for their actions. However, because the actions of the Defendants have deeply disturbed the public, especially the container trailer truck drivers, especially the actions of the Defendants are also contrary to the applicable regulations, the Public Prosecutor submits the Defendants to trial for later examination and trial by the Panel of Judges in the fairest way possible. The application of corporate criminal responsibility to thuggery, in this case the Panel of Judges sentenced the Defendants who were involved in one unit to PT. Tanjung Raya Kemilau, meaning, in this case the Panel of Judges applies the first model of the theory of corporate responsibility proposed by Mardjono Reksodiputro, namely "Corporate Management as the maker and the administrator is responsible", while still aligning the theory and the applicable legal rules contained in Article 48, Article 49, Article 50, Article 56, Article 486, Article 487 and Article 595 of the latest Draft Criminal Code. Thus, as one of the law enforcement officers, the panel of judges has carried out their duties in accordance with applicable regulations.